Vector error correction model in explaining the association of some macroeconomic variables in Indonesia - Adnan, Adnan; Tedja, Enriko (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2023)
The purpose of this article is to empirically analyze the long and short runs association of some macroeconomic variables in Indonesia by looking at macroeconomic and fiscal indicators as variables that influence each other in the creation of a stability investment climate, using the Vector Error Correction model (VECM). Based on the VECM interpretation carried out, the inflation variable most affects the shock (movement) of Foreign Direct Investment with a positive impulse. While the Variable Foreign Direct Investment itself most affects Employment, GDP Growth, and Tax Revenue with a positive impulse, then for inflation variables and interest rates are most influenced by employment variables with positive impluse. Thus, foreign direct investment has a crucial role and many other variables, namely long-term influence on employment, GDP growth, and tax revenue, indicating that foreign direct investment is the main source in shoring up macroeconomic and fiscal stability in Indonesia. Thus, policies on employment, GDP growth and tax revenue should consider efforts to increase foreign direct investment, because the greater the increase in foreign direct investment will result in positive shock on all three variables